Technology Integration of the In-Service EFL Teachers: A Study at a Teacher Profession Education Program - Fatimah Tuzahra; Sofendi Sofendi; Machdalena Vianty (Indonesian Journal of EFL and Linguistics, 2021)
Utilizing technology in the classroom characterizes the 21st century teachers. Therefore, teachers are demanded to be able to use technology in pedagogical practices in order to fulfill their students’ needs facing rapidly digitalized life. This study was designed to investigate the perceptions of a group of in-service English as Foreign Language (EFL) teachers who studied at a Teacher Profession Education program at a state university, concerning the application of technology within challenges they faced during their study. This study used qualitative research with narrative approach as a strategy of inquiry. The data were obtained by using a semi-structure interview with the in-service teachers and documentation. The data were analyzed using thematic analysis. The results of the study showed that the participants generally perceived positively the technology integration taught by their university instructors during their study time at the Teacher Profession Education program although there was a negative response when they were firstly introduced with the technology. It might have been caused by their lack of technological knowledge. The result also revealed that the participants found it challenging when it came to the use of novel technology as introduced and applied by their university instructors. In addition, their own integration of technology during their Teaching Practice was a challenge due to the students’ low motivation to engage in the online learning activity which was the mode of learning. The findings of this study suggest that teachers need to advance their skills and knowledge to utilize technology in supporting their pedagogical practices.